Florida Strawberry Production Costs and Trends - Zhengfei Guan; Feng Wu; Alicia J. Whidden (EDIS)
To help growers and policy makers understand how and why strawberry production costs have changed over time, this 5-page fact sheet written by Zhengfei Guan, Feng Wu, and Alicia Whidden and published by the UF/IFAS Food and Resource Economics Department presents cost information collected over a five-year period, analysis of the cost structure of Florida strawberries, and an examination of the trend of changing costs along with the factors underlying the trend. http://edis.ifas.ufl.edu/fe1013